Accessible and cost-effective methods for patterning cell monolayers on compliant substrates - Molly McCord; Aimal H. Khankhel; Katherine Kafkis; Griffin Radtke; Sinan Candan; Hareesh Ashok Kumar; Pieter Derksen; Michelle Tam; Kaiyan Zhou; Markus W. Merk; Christian Franck; Sebastian J. Streichan; et al. (PLoS ONE, 2026)
Micropatterning is a versatile technique for confining single cells and cell monolayers to a particular size or shape. The resulting geometrical confinement is one means of controlling migration, differentiation, and force generation. As such, micropatterning is a valuable tool for studying the principles governing collective cell behavior, tissue morphogenesis, and other questions in mechanobiology. Here, we present two detailed and accessible protocols for micropatterning cell monolayers onto compliant substrates made of a polyacrylamide hydrogel and a polydimethylsiloxane elastomer. These protocols require minimal specialized equipment, making them broadly accessible. We validate the fidelity of our protocols across a range of confinement geometries. Furthermore, we demonstrate an example application of our hydrogel protocol to traction force microscopy, which allows for investigating effects of geometric confinement on cell-generated forces. Together, these protocols provide detailed, reproducible tools to support the widespread application of micropatterning in studies of mechanobiology and collective cell dynamics.